Il croato molisano - Kovačić, Vinko; Sammartino, Francesca (Linguistik Online, 2025)
The present contribution aims at illustrating the Molise Croatian (called by native speakers na-našo, na-našu, naš jezik), a historical minority language spoken by above 1,000 people in the Southern Italian region Molise, nowadays in the three points Acquaviva Collecroce (Kruč), Montemitro (Mundimitar) and San Felice del Molise (Filič). This paper illustrates the status, history, literary production, linguistic traits and protection of Molise Croatian. Nowadays Molise Croatian is an endangered language that structurally undergoes the linguistic contact with Italian and whose speakers are decreasing in number, despite a strong awareness and protection given by both the speakers and the institutions.